Simplifying life cycle Assessment: Basic considerations for approximating product carbon footprints based on corporate carbon footprints - Maximilian Schutzbach; Robert Miehe; Alexander Sauer (Ecological Indicators)
The increasing prevalence of sustainability regulations has increased the demand for ecological assessment at both the company and product levels. However, calculating individual product carbon footprints (PCF) for each product remains impractical for companies, especially with extensive and heterogeneous product portfolios, due to the high effort, complexity, and data intensity involved. As a result, research and industry are increasingly focusing on simplifying PCF calculations. While various approaches exist, one key shortcoming remains: the synergies between corporate carbon footprint (CCF) and PCF calculations are not fully utilized. Leveraging these synergies through an integrated approach and the systematic use of shared databases could significantly reduce effort. This article addresses this gap by proposing basic considerations that enable PCF approximation based on a CCF. A comprehensive analysis of the state of the art and identifying seven key challenges in deriving PCFs from CCF led to the formulation of nine requirements for a process model. Based on these requirements, a conceptual process model is developed aligned with the principles of ISO 14067. This model facilitates the approximation of PCFs within the cradle-to-gate system boundary, leveraging existing CCF data. This work proposes an initial basis for efficient and standardized CCF and PCF calculations by providing a concept for a structured approximation method, which contributes to the overarching goal of harmonizing sustainability assessments in corporate practice. However, the presented process model requires further refinement and, above and beyond this, practical validation.